William James and 18th-century anthropology: Holism, scepticism and the doctrine of experience. (July 2018) - Carroll, Jerome
This article discusses the common ground between William James and the tradition of philosophical anthropology. Recent commentators on this overlap have characterised philosophical anthropology as combining science (in particular biology and medicine) and Kantian teleology, for instance in Kant's seminal definition of anthropology as being concerned with what the human being makes of itself, as distinct from what attributes it is given by nature. This article registers the tension between Kantian thinking, which reckons to ground experience in a priori categories, and William James's psychology, which begins and ends with experience. It explores overlap between James's approach and the characteristic holism of 18th-century philosophical anthropology, which centres on the idea of understanding and analysing the human as a whole, and presents the main anthropological elements of James's position, namely his antipathy to separation, his concerns about the binomial terms of traditional philosophy, his preference for experience over substances, his sense that this holist doctrine of experience shows a way out of sterile impasses, a preference for description over causation, and scepticism. It then goes on to register the common ground with key ideas in the work of anthropologists from around 1800, along with some references to anthropologists who come in James's wake, in particular Max Scheler and Arnold Gehlen, in order to reconceptualise the connection between James's ideas and the tradition of anthropological thinking in German letters since the late 18th-century, beyond its characterisation as a combination of scientific positivism and teleology.